2018
DOI: 10.1159/000488047
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Non-Invasive Limb Ischemic Preconditioning Confers Cardioprotection Through PKC-Ԑ/STAT3 Signaling in Diabetic Rats

Abstract: Background/Aims: Protein kinase C(PKC)-ε activation is a mechanism of preconditioning cardioprotection but its role in repeated non-invasive limb ischemic preconditioning (rNLIP) mediated cardioprotection against myocardial ischemia/reperfusion (I/R) injury in diabetes is unknown. Methods: Eight-week streptozotocin-induced diabetic and non-diabetic Sprague-Dawley rats were subjected to I/R without or with rNLIP. In vitro, H9C2 cells were cultured with high glucose (HG) and subjected to hypoxia/re-oxygenation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 47 publications
4
36
2
2
Order By: Relevance
“…After five weeks of diabetes induction, they found that myocardial STAT3 activation (at the Ser727 site) was lower in the diabetic group. Later the same research group confirmed these results in STZ-induced type I diabetes models [ 29 , 30 ] and demonstrated that phosphorylation and activation of STAT3 at Tyr705 was also decreased in diabetes [ 29 , 30 , 31 ]. Besides type I diabetes models, reduction of cardiac STAT3 expression was also described in a type II diabetes model, i.e., STAT3 mRNA was downregulated in non-obese Goto-Kakizaki rats [ 25 ].…”
Section: Effect Of Cardiovascular Risk Factors On Cardiac Stat3 Unmentioning
confidence: 80%
See 1 more Smart Citation
“…After five weeks of diabetes induction, they found that myocardial STAT3 activation (at the Ser727 site) was lower in the diabetic group. Later the same research group confirmed these results in STZ-induced type I diabetes models [ 29 , 30 ] and demonstrated that phosphorylation and activation of STAT3 at Tyr705 was also decreased in diabetes [ 29 , 30 , 31 ]. Besides type I diabetes models, reduction of cardiac STAT3 expression was also described in a type II diabetes model, i.e., STAT3 mRNA was downregulated in non-obese Goto-Kakizaki rats [ 25 ].…”
Section: Effect Of Cardiovascular Risk Factors On Cardiac Stat3 Unmentioning
confidence: 80%
“…Moreover, similar trends were observed in in vitro models of diabetes. In H9c2 cells subjected to high glucose conditions (25 mM glucose added to the medium), the non-ischaemic baseline STAT3 phosphorylation (Tyr705 and/or Ser727) and activation was significantly decreased [ 29 , 32 ]. Similarly, exposure of isolated adult rat ventricular cardiomyocytes to high glucose conditions also resulted in reduced non-ischaemic baseline phosphorylation and activation of STAT3 (Tyr705) [ 33 ].…”
Section: Effect Of Cardiovascular Risk Factors On Cardiac Stat3 Unmentioning
confidence: 99%
“…For the mechanisms involved, RIPC‐induced cardioprotective effects are, at least in part, dependent on exosomes which significantly accumulate in the plasma during RIPC and subsequently alleviate myocardial I/R injury via their antiapoptotic properties (Minghua et al, ; Vicencio et al, ). In addition, other related mechanisms have been revealed, such as protein kinase C‐ε (PKC‐ε) overexpression (C. Wang et al, ), STAT5‐dependent antiapoptotic signaling pathway induction (H. Chen et al, ) and glucagon‐like peptide‐1 activation (Basalay et al, ).…”
Section: Hsp70: Involvement In Conditioning Against Myocardial I/r Inmentioning
confidence: 99%
“…As an essential component of the survivor activating factor enhancement pathway, activation of STAT3 signaling has been implicated in protecting the heart from myocardial I/R injury under both ischemic pre-or post-conditioning protocols and basal conditions. [32][33][34][35] Mice with cardiac-specific knockout of STAT3 develop significantly greater myocardial IS within the left ventricle, which is associated with increased cardiac apoptosis, reduced cardiac function, and reduced survival. 36 In contrast, cardiac-specific transgenic mice expressing STAT3 exhibit reduced myocardial IS and cardiomyocyte apoptosis when compared with non-transgenic littermates.…”
Section: Discussionmentioning
confidence: 99%